Influence of Historical Accounts on Contemporary Foreign Policy Making - Usiemure, Christopher; Etor, Charity (Advances in Humanities and Contemporary Studies, 2025)
This paper attempts to determine the extent to which historical accounts influence contemporary foreign policy making. By reviewing a meticulous reading of historical narratives and its implication in the creation of diplomatic judgment-making behaviours, the present research offers insight into the intricate link between historical memory, national character, and policy demands in foreign policy development. Findings indicate that historical accounts function as knowledge reservoir that policymakers draws from to make inferences regarding previous events, schemes, and connections to frame their policy activities. This article has underscored the difficulty of capturing historical events and addressing surrounding disparities, calling into the past, while outlining them in a modern context. This research sheds light on the enduring significance of historical narratives in guiding foreign policy decisions and fostering constructive international relations.